PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA PEGAWAI PADA DITJEN PERHUBUNGAN UDARA BAGIAN KSHUM - Aris Budiono; Desi Wuryandari (Human Capital Development, 2017)
Purpose- This research aims to know the impact of work environment and compensation on employee’s motivation at a division of Directorate General of Air Transportation. Design/methology/approach- The research conducted a survey by the questionnaire to the employees. Totally there were 20 respondents as samples in this research for the validity test. By non probability sampling method, the respondents are 65 persons. The method on analysis by descriptive. To examine the impact of work motivation and work environment, the author used multiple linear regression analysis with F test and t test. Findings- The results. by t-test, it was found that the work environment had a significant impact on the improvement of work motivation of the employees. While work environment variable can increase work motivation. Compensation also affects the employee's work motivation . While, both variables, simultaneously, found that Work Environmen and Compensation have significantly contributed to work motivation. Other factors include leadership, quality of human resources, organizational culture, work performance, are not included in this research that need to a further research. Originality – At this Government Agency, the two variables are in need to support productivity of employees.